Inductive Power Transfer to Charge Electric Bicycles - Revathi Shree, K.; J. Yamuna; K. Sahana; M. Chandrika; Sarin, M. V. (Asian Journal of Electrical Sciences, 2019)
Inductive power transfer is nothing but wireless power transfer. That is transferring power from transmitter to receiver side without any physical contact. Nowadays this technique has wide applications. Mainly it is used to charge the batteries of the electric vehicles (EV). Due to the increasing pollution rate and scarcity of fuel in future days, the demand for the electric vehicles is increasing. Charging EV’s using IPT is simpler and risk free when compared to traditional wired charging systems. Using IPT technique the battery can be charged in constant current (CC) and constant voltage (CV) modes without using any feedback. A switch (consists of 2 AC switches and capacitor) is used to change the mode from CC to CV. The current output from the CC and the voltage output from the CV mode are load independent. This can be obtained by proper selection of inductances and capacitors. Here the feedback control techniques are not required to regulate the output according to charging profile. This IPT technique to charge battery is economical because using a single inverter many batteries can be charged at a time. The possibility of this method of charging is tested with an experimental prototype for efficiency and using MATLAB/SIMULINK software the simulation results are obtained for stability of current and voltage output of CC and CV mode.